Breeding for plant‐based proteins in pulse and legume crops: Perspectives, challenges and opportunities - Cordoba, H. A.; Sadohara, R.; Gali, K. K.; Zhou, J.; Hart, J.; Alexandre, A. C. Silveira; Cichy, K.; Wilker, Jennifer; Dohle, S.; Mukankusi, Clare; Warkentin, T. D.; Rajcan, I.; et al. (Wiley, 2025)
Abstract The consumption of plant proteins is increasing worldwide as a viable alternative to animal‐derived proteins in the marketplace. The projected increase in global population to at least 10 billion by 2050 is placing greater pressure on the food supply, particularly due to the rising demand for large‐scale protein production. This protein transition is caused by macro‐drivers such as changing consumer demographics, environmental sustainability, animal ethics, regulatory influences, and changing dietary patterns. Research efforts worldwide have explored various food applications for plant protein ingredients, including meat analogs, dairy alternatives, beverages, bakery products, and hybrid products. We provide here a review of the potential for legume breeding programs to incorporate traits that target the emerging plant‐based protein market and aim to promote discussion among (but not limited to) plant breeders and geneticists, plant physiologists, agricultural economists, food scientists and chemists, and agricultural engineers. The prospects, progress, and tools developed when breeding for protein content, quality, structure, and functionality of several food legumes (common bean— Phaseolus vulgaris , pea— Pisum sativum , lentil— Lens culinaris , chickpea— Cicer arietinum , faba bean— Vicia faba , and mung bean— Vigna radiata ) are presented. We also present some of the physiological processes that affect the accumulation of nitrogen and protein metabolism in tropical legume crop species, providing some insight into potential breeding targets for improving protein concentration, quality, and structural and functional properties. Finally, a perspective of industrial processing technologies for extracting and transforming plant proteins is discussed.